KEUNGGULAN PERAN EXPERIENTIAL MARKETING DALAM MENCIPTAKAN CONSUMER SATISFACTION - Jubery Marwan (KELOLA: Jurnal Ilmiah Manajemen, 2022)
The superiority of the role of experiential marketing in creating consumer satisfaction is largely determined by the role of celebrity endorsement and word of mouth in the equation format of the research model. the role of celebrity endorsement and word of mouth in advertising to build product/service introductions in understanding the functions and characteristics of products/services. An endorser is selected from a reference group who is considered to have the ability to serve as a role model for the target market so that apart from acting as an information provider, he communicates the value features of the product/service benefits through the application of media technology but can also persuade consumers to make a purchase. On the other hand, word of mouth plays a role in disseminating product/service information massively through social media such as YouTube, WhatsApp, Line, Google, Facebook, and other applications on devices connected to other internet connections, and forming a network (buzzer) that can create customer satisfaction. Because word of mouth activities are based on a person's experience in consuming a pleasant product or service. This research method uses a quantitative approach and is included in the type of explanatory research sourced from the results of the analysis of processed primary data. Data was obtained through a survey by distributing questionnaires using a Likert scale as an alternative to respondents' answers. The analysis of the model equation using path analysis aims to test and analyze the advantages of the role of experiential marketing in creating consumer satisfaction through celebrity endorsement and word of mouth as intervening variables. The results of the analysis show that; 1) The experiential marketing variable has a significant positive effect on celebrity endorsement and word of mouth; 2) The role of experiential marketing variables is proven to be able to create consumer satisfaction indirectly through celebrity endorsement variables and word of mouth.